Does Femoral Head Translation Vary by Sex and Side in Asymptomatic Hips During a Weightbearing Apprehension Test?. Issue 6 (23rd June 2022) - Ruh, Ethan; Johnson, Camille; Frankston, Naomi; Charles, Shaquille; Anderst, William; McClincy, Michael
Abstract: Background: Hip microinstability is an increasingly recognized source of pain and dysfunction but has no agreed upon diagnostic criteria and the pathophysiology remains unclear. It has been suggested that pain associated with microinstability is caused by excess translation of the femoral head. Recent research indicates that single-plane femoral head translation can be reliably measured using dynamic ultrasonography during a supine clinical examination; however, the overall accuracy of that technique has not been established, and the range of femoral head translation values that are found in individuals with no history of surgery or symptomatic pathology is unknown. Questions/purposes: (1) How much femoral head translation is present in native, uninjured hips during a weightbearing apprehension position for females and males? (2) How large is the side-to-side difference in hip translation and rotation within the same individual in females and males with no history of surgery or pain during the weightbearing apprehension position? (3) What differences exist in femoral head translation and rotation when comparing females to males? Methods: Twenty-two young adults (11 males, 11 females; mean age 22 ± 2 years; BMI 22 ± 5 kg/m 2 ) with no history of hip pain, no known hip injury, and who never had hip surgery participated in this study. High-resolution CT images of the femur and pelvis were acquired for each participant, and the bone tissue was segmented from the CT volume. Synchronized biplane radiographs were collected during a neutral standing trial and during a static weightbearing apprehension position in which the participant extended, externally rotated, and abducted at their back hip while standing with their feet split in the AP direction. A validated volumetric model-based tracking technique was used to match the patient-specific bone models to the biplane radiographs with an accuracy of 0.3 mm for translation and 0.8° for rotation. Translation of the center of the femoral head relative to the center of the acetabulum and rotation of the femur relative to the pelvis from neutral to the weightbearing apprehension position were calculated. Sex-based differences in hip kinematics were assessed by bivariate linear regression. Results: The median (range) translation during the weightbearing apprehension position in females was 0.9 mm (0.2 to 2.7 mm), which was less than in the 1.3 mm (0.2 to 2.6 mm) translation found in males (median difference of 0.5 mm; p = 0.04). The median absolute side-to-side difference in translation during the pivot was 1.4 mm (0.1 to 3.8 mm) in females and 1.3 mm (0.1 to 4.4 mm) in males. Conclusion: These findings demonstrate that the femoral head translates the same under bodyweight loading as previously observed during supine exam, showing the inherent stability of the hip with no history of surgery or symptomatic pathology. This study also provides normal values for comparison with individuals who have suspected microinstability. Future directions for research include directly comparing biplane radiography to alternative imaging techniques, such as dynamic ultrasound, for identifying hip microinstability and identifying threshold values for symptomatic hip microinstability. Level of Evidence: Level III, prognostic study.